The CENDARI infrastructure in GIS-based historical research. Issue 2 (4th July 2017) - Moscicka, Albina Kinga
Abstract : Purpose: The purpose of this paper is to propose a way of using already existing archival resources in the geographic information system (GIS). Design/methodology/approach: The essence of the methodology used was to identify semantic relations of archival documents with geographical space and develop their metadata into spatially related metadata, ready to use in GIS and to join geographical names occurring in these metadata with exact places to which they were related to. Research was based on two digital collections from the Library of Contemporary History in Stuttgart on-line service. These collections were related to the First World War and they included metadata prepared in MAB standard. Findings: As the results of the research, two sample metadata sets related to posters and ration coupons were developed. Thesauruses of coordinates of places and regions mentioned in documents metadata in different semantic context were also created. To complete the methodology, the assumptions of the GIS structure and concept of applying metadata in them, have been proposed. Research limitations/implications: The research also presents limitations in effective implementation of the proposed solutions, which lie mainly in lack of rules and consequences in recording geographical names in metadata. Originality/value: The value of the proposed solution is easy way of using already existing data in GIS and possibilities of gathering, managing, presenting and analyzing archives with one parameter more than in traditional databases – with spatial information. The added value and an effective use of already collected data lies in the strong recommendation of defining and implementation of rules for recording geographical names in archival documents metadata. This will help in a wide use of collected data in any spatial-based solutions as well as in automation of process of joining archives with geographical space, and finally in dissemination of collected resources.